Portable heat pump testing device - Kłosowiak, Robert; Bartoszewicz, J; Urbaniak, Rafał (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to present the design and working principle of a portable testing device for heat pumps in the energy recirculation system. The presented test stand can be used for any refrigerating/reverse flow cycle device to calculate the device energy balance. The equipment is made of two portable containers of the capacity of 250 liters to simulate the air heat source and ground heat source with a system of temperature stabilization, compressor heat pump of the coefficient of performance (COP) of = 4.3, a failsafe system and a control and measurement system.
Keywords: heat pumps; renewable energy; coefficient of performance (COP)